Metabolism of Nanomaterials in Vivo: Blood Circulation and Organ Clearance - Wang, Bing; He, Xiao; Zhang, Zhiyong; Zhao, Yuliang; Feng, Weiyue (Accounts of chemical research, 2013)
Before researchers apply nanomaterials (NMs) in biomedicine, they need to understand the blood circulation and clearance profile of these materials in vivo. These qualities determine the balance between nanomaterial-induced activity and unwanted toxicity. NMs have heterogeneous characteristics: they combine the bulk properties of solids with the mobility of molecules, and their highly active contact interfaces exhibit diverse functionalities. Any new and unexpected circulation features and clearance patterns are of great concern in toxicological studies and pharmaceutical screens. A number of studies have reported that NMs can enter the bloodstream directly during their application or indirectly via inhalation, ingestion, and dermal exposure. Due to the small size of NMs, the blood can then transport them throughout the circulation and to many organs where they can be stored. In this Account, we discuss the blood circulation and organ clearance patterns of NMs in the lung, liver, and kidney. The circulation of NMs in bloodstream is critical for delivery of inhalable NMs to extrapulmonary organs, the delivery of injectable NMs, the dynamics of tissue redistribution, and the overall targeting of drug carriers to specific cells and organs. The lung, liver, and kidney are the major distribution sites and target organs for NMs exposure, and the clearance patterns of NMs in these organs are critical for understanding the in vivo fate of NMs. Current studies suggest that multiple factors control the circulation and organ clearance of NMs. The size, shape, surface charge, surface functional groups, and aspect ratio of NMs as well as tissue microstructures strongly influence the circulation of NMs in bloodstream, their site-specific extravasation, and their clearance profiles within organs. Therefore structure design and surface modification can improve biocompatibility, regulate the in vivo metabolism, and reduce the toxicity of NMs. The biophysicochemical interactions occurring between NMs and between NMs and the biological milieu after the introduction of NMs into living systems may further influence the blood circulation and clearance profiles of NMs. These interactions can alter properties such as agglomeration, phase transformations, dissolution, degradation, protein adsorption, and surface reactivity. The physicochemical properties of NMs change dynamically in vivo thereby making the metabolism of NMs complex and difficult to predict. The development of in situ, real-time, and quantitative techniques, in vitro assays, and the adaptation of physiologically-based pharmacokinetic (PBPK) and quantitative structure–activity relationship (QNSAR) modeling for NMs will streamline future in vivo studies.